(untitled) - Batiza, Ann Finney (Hoboken, 2007)
The Third Edition of this landmark text offers an authoritative, accessible, and engaging introduction to modern, genome-centered biology from its foremost practitioners. The new edition explores core concepts in molecular biology in a contemporary inquiry-based context, building its coverage around the most relevant and exciting examples of current research and landmark experiments that redefined our understanding of DNA. As a result, students learn how working scientists make real high-impact discoveries.
Keywords: Bioinformatics.,Computational Biology.,Genomics,Sinh học máy tính; Popular